Pengembangan Aplikasi Event Management Multi-Platform Dengan Sistem Rekomendasi Berbasis Rule-Based Hybrid Filtering - Juliansyah, Arman; Ratnasari, Anita (Teknik Informatika Fakultas Ilmu Komputer, 2026)
The rising demand for skill development through workshops calls for a platform that efficiently manages events while personalizing user experiences. This study presents a multi-platform event management application featuring a rule-based hybrid recommendation system tailored to user interests, skill levels, and location. Developed using Agile Kanban, the system employs Laravel for the backend RESTful API and Flutter for the mobile frontend. Core features include QR-based attendance, discussion forums, and analytical dashboards. The recommendation engine combines content-based and collaborative filtering using predefined rules, enabling lightweight, transparent, and accurate personalization without machine learning. Testing confirmed that the core features function effectively and improve the experience for both users and organizers. The platform addresses inefficiencies in manual event handling and offers a scalable, user-focused solution for skill-based education. This system supports the digital transformation of event management by offering intelligent features tailored to participant profiles and needs.